The Signaling Role of Politician Stock Ownership: Effects on Lobbying Intensity. (May 2018) - Ridge, Jason W.; Hill, Aaron D.; Ingram, Amy
Adopting a signaling theory perspective, we argue that politician stock ownership sends signals of positive predispositions to firms, thereby alleviating some necessity for firms to emphasize lobbying expenditures to influence political action. Using data on congressional stock ownership, we find support for our arguments. We find that as the proportion of Congress owning stock in a firm increases, the firm decreases the intensity of lobbying. Furthermore, we find that the signals associated with stock-holding politicians with greater ability to affect the legislative agenda (i.e., affiliation with the majority party) relates to lobbying intensity. Our findings add to the literature on lobbying while also offering implications for practice and avenues for future research.